PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PENINGKATAN KINERJA KESELAMATAN DAN KESEHATAN KERJA (K3) DI PT. XYZ - Silalahi, Andrew F.C. (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Good Corporate Governance has an important role in facilitating communication between company organs, relations between the company and shareholders and other stakeholders as well as ensuring the company's compliance with laws and regulations. Good of Corporate Governance PT. XYZ has the function of establishing, developing, directing and strategizing in the implementation of company compliance related to the implementation of Good Corporate Governance to support the achievement of the Vision and Mission of PT. XYZ while still paying attention to the principles of Corporate Ethical Standards, Good Corporate Governance, and company values. Efforts made by management in managing the company will increase profits and reduce the risk of losses in the future. The higher the value of the company, the more prosperous the shareholders and employees of the company will be. The purpose of this study was to see the influence of the implementation of Good Corporate Governance (GCG) on the Improvement of Occupational Health and Safety Performance at PT. XYZ. The population in this study are agro-industrial companies for the period 2020 to 2022. The data analysis technique uses descriptive qualitative. The research was conducted in the city of Jakarta on the basis that this city is the center of agro-industrial companies. The results of the study show that the implementation of Good Corporate Governance consistently has a positive effect on improving Occupational Health and Safety (K3) performance at PT. XYZ. This has a positive impact on employee work productivity which certainly has a positive effect on improving company performance.